2005
DOI: 10.1590/s1516-635x2005000200009
|View full text |Cite
|
Sign up to set email alerts
|

Time required to protect the intestinal tract of chicks against Salmonella enterica serovar enteritidis using competitive exclusion

Abstract: Competitive exclusion (CE) has been designed to accelerate the colonization of the alimentary tract of young commercial birds and it has been also used to repopulate the digestive tract after antibiotic therapy. The method has been successfully adopted as a means to prevent enteric salmonellosis. The present study was carried out to evaluate if CE is able to prevent this kind of infection. Newly hatched chicks were given a CE culture and at different intervals of time birds infected with Salmonella Enteritidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Sterzo et al, (2005) reported that bacteria present in the hatchery determine the colonization of beneficial or pathogenic bacteria. Cukrowska et al (2002) showed that pathogens can be lodged in the chick´s intestine and colonize in the first contact with microbes in the hatchery, so it is necessary to inoculate probiotic bacteria before the chick and hen can be in contact.…”
Section: Introductionmentioning
confidence: 99%
“…Sterzo et al, (2005) reported that bacteria present in the hatchery determine the colonization of beneficial or pathogenic bacteria. Cukrowska et al (2002) showed that pathogens can be lodged in the chick´s intestine and colonize in the first contact with microbes in the hatchery, so it is necessary to inoculate probiotic bacteria before the chick and hen can be in contact.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting study demonstrated that the time of initial intestinal colonization by desirable bacteria play an important role on the colonization of pathogens [1] . In the previous studies [4][5][6]8,12] , the protection effects of in ovo inoculation or other route administration of probiotics against Salmonella infection were investigated, but the effects of inoculation of different probiotic strains on intestinal morphometry, and goblet cells count have not been attended.…”
Section: Majidi-mosleh Sadeghi Mousavi Chamani Zareimentioning
confidence: 99%
“…In the modern poultry production, the contact between newborn chicks and hens is excluded, and colonization of bacteria in the gut depends on the type of bacteria present in the hatchery environment [1] . This condition exposes chicks to pathogenic bacteria colonization in the gut and causes a delay in desirable bacteria colonization [2] .…”
Section: Introductionmentioning
confidence: 99%
“…CE is designed to accelerate the intestinal tract colonization of young com-mercial birds and also repopulate the gastrointestinal tract after receiving antibiotics. The application of CE culture prepared from adult laying feces has been showed to reduces Salmonella infection (Sterzo et al 2005). The using of CE product in broiler chickens provides a protection from Salmonella infection, improve the broiler performance and improve the intestinal histology…”
Section: Introductionmentioning
confidence: 99%